Synthesis of thinned concentric ring array antenna in predefined phi‐planes using binary firefly and binary particle swarm optimization algorithm. (20th March 2014) - Chatterjee, Anirban; Mahanti, G. K.; Mahanti, Ananya
Abstract A binary firefly algorithm inspired by the behavior of artificial fireflies has been applied to thin a planar concentric ring array antenna to minimize the peak sidelobe level in a number of predefined ϕ‐planes. Two different cases comprising two different design specifications for the optimized thinned array have been considered. In the first case, the array is thinned to reduce the peak sidelobe level while keeping the first null beamwidth and half power beamwidth of the array below their specified values in all the defined ϕ‐planes. In the second case, peak sidelobe level of the array is reduced regardless of any pre‐specified values of first null beamwidth and half power beamwidth. To illustrate the superiority of binary firefly algorithm, the thinning of the array for the two different cases has been compared with binary particle swarm optimization algorithm. Results clearly show the superiority of binary firefly algorithm in finding optimum solutions for both cases. Copyright © 2014 John Wiley & Sons, Ltd.